Honeycomb core-shell structure composite material nano-catalyst and preparation method and application thereof

A honeycomb core-shell structure composite nanocatalyst, formed by modifying ZSM-5 zeolite with alkali and acid treatment and doping with Ni, Cu, and Co, addresses the low surface area issue of spinel materials, achieving high methanol decomposition and hydrogen conversion rates.

CN119236998APending Publication Date: 2025-01-03TIANFU YONGXING LAB
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411333620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The catalytic activity of spinel materials is limited by their small specific surface area, which hinders their effectiveness in hydrogen production processes.

Method used

A honeycomb core-shell structure composite nanocatalyst is prepared by modifying small-grain ZSM-5 zeolite with alkali and acid treatment, followed by doping with Ni, Cu, and Co to form a core-shell structure, enhancing the specific surface area and defect sites for improved catalytic activity.

Benefits of technology

The composite nanocatalyst significantly increases the specific surface area to 342.763 m²/g, achieving 83% methanol decomposition and 91.3% hydrogen conversion at 280°C, demonstrating enhanced catalytic performance in hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236998A_ABST
    Figure CN119236998A_ABST
Patent Text Reader

Abstract

The invention discloses a honeycomb core-shell structure composite material nano-catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalyst materials. The method comprises the following steps: adding small-grain ZSM-5 zeolite into a NaBH4 aqueous solution, heating, stirring and drying; grinding, pickling and drying the dried product, and then grinding again to obtain modified small-grain ZSM-5 zeolite; the preparation method comprises the following steps: dissolving Ni (NO3) 2.6 H2O, Cu (NO3) 2.3 H2O, Co (NO3) 2.6 H2O and urea into a mixed solvent, and magnetically stirring; transferring the obtained mixed solution into a reaction kettle, adding the modified small-grain ZSM-5 zeolite powder, sealing, heating, and cooling at room temperature; and washing the obtained solid material with deionized water and ethanol, centrifuging, and sequentially drying and calcining the centrifuged material to obtain the product. The catalyst provided by the invention has excellent performance in hydrogen production through methanol decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst materials and relates to a honeycomb core-shell structure composite material nanocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen production is gaining importance as a better alternative to processes based on the use of traditional fossil fuels. Researchers around the world are working on developing various technologies for hydrogen production, such as water electrolysis, steam reforming, etc.

[0003] Spinel is one of the commonly used catalytic materials for hydrogen production. Its molecular formula is AB2O4. 2+ It is a four-coordinate ion, forming a tetrahedron, B 3+ It is a six-coordinate ion, forming a regular octahedron. Co3O4 is a simple spinel, whose A-site ion and B-site ion belong to the same element. However, its activity is not satisfactory in catalytic reactions. The specific surface area of ​​spinel materials is very small, which limits the catalytic activity.

[0004] Therefore, how to develop a honeycomb core-shell structure composite material nanocatalyst with improved catalytic activity and its preparation method and application is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0005] In view of this, the present invention provides a honeycomb core-shell structure composite material nanocatalyst and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a honeycomb core-shell structure composite material nanocatalyst comprises the following steps:

[0008] (1) adding small-grain ZSM-5 zeolite into a NaBH4 aqueous solution, heating and stirring, and drying;

[0009] (2) grinding the dried product to a particle size of 40-60 mesh, adding it to an oxalic acid solution and stirring it for pickling, and then drying it and grinding it again to a particle size of 200-600 nm to obtain a modified small-grain ZSM-5 zeolite;

[0010] (3) dissolving Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O and urea in a mixed solvent at a molar ratio of 0.75:0.25:2:10, and stirring magnetically to obtain a mixed solution;

[0011] (4) transferring the obtained mixed solution to a reaction kettle, adding the obtained modified small-grain ZSM-5 zeolite powder, sealing and heating, and cooling at room temperature to obtain a solid material;

[0012] (5) The obtained solid material is washed with deionized water and ethanol for several times, then centrifuged to remove the supernatant, and the centrifuged material is dried and calcined in sequence to obtain the honeycomb core-shell structure composite material nanocatalyst.

[0013] Furthermore, in step (1), the concentration of the NaBH4 aqueous solution is 4 wt%, and the mass ratio of the small-grain ZSM-5 zeolite to the NaBH4 aqueous solution is 1:40.

[0014] The beneficial effect of adopting the above further technical solution is that the alkali solution modification can etch a rough porous structure on the surface of the molecular sieve to facilitate the growth of spinel on the surface of the molecular sieve. Without this step, part of the zeolite surface cannot be used for spinel growth.

[0015] Furthermore, in step (1), the silicon-aluminum ratio of the small-grain ZSM-5 zeolite is 100-250, and the grain size is 200-600 nm.

[0016] Furthermore, in step (1), the heating and stirring temperature is 80° C., the heating and stirring time is 2 hours, the heating and stirring speed is 300 rpm, the drying temperature is 100° C., and the drying time is 2 hours.

[0017] Furthermore, in step (2), the concentration of the oxalic acid solution is 1 mol / L, and the mass volume ratio of the dried product to the oxalic acid solution is 0.8 g:40 mL.

[0018] The beneficial effect of adopting the above further technical solution is that acid washing can wash away the molecular sieve fragments etched by alkali solution to ensure the specific surface area of ​​the molecular sieve. If this step is not taken, the etched molecular sieve fragments will block the pores, resulting in a reduction in the specific surface area.

[0019] Furthermore, in step (2), the stirring time is 1 hour, the stirring speed is 300 rpm, the drying temperature is 100° C., and the drying time is 2 hours.

[0020] Furthermore, in step (3), the mixed solvent is deionized water and ethanol in a volume ratio of 3:1, 1 mmol of urea is dissolved in 6 mL of the mixed solvent, the magnetic stirring time is 25 min, and the stirring speed is 300 rpm.

[0021] Furthermore, in step (4), the mass ratio of the mixed solution to the modified small-grain ZSM-5 zeolite powder is 62:0.6, the heating temperature is 180°C, the heating time is 12h, and the mixture is cooled to 25°C from room temperature.

[0022] Furthermore, in step (5), the drying temperature is 80° C., the drying time is 2 h, the calcination temperature is 400° C., and the calcination time is 2 h.

[0023] Furthermore, in step (5), the centrifugal speed is 4000 rpm and the centrifugal time is 3 min.

[0024] The invention also provides a honeycomb core-shell structure composite material nanocatalyst prepared by the method.

[0025] The present invention also provides an application of the honeycomb core-shell structure composite material nanocatalyst in hydrogen production by methanol degradation.

[0026] The beneficial effects of the present invention are:

[0027] The present invention prepares a modified solid solution by doping and replacing the A position of AB2O4 spinel, and XRD and XPS results confirm that the surface defects of the solid solution are significantly improved. EDS scanning spectrum confirms that the element content in the solid solution is in line with expectations. SEM images show that as the a-position atom is replaced, the morphology of the spinel changes from a cubic shape to a flower shape, resulting in an increase in the specific surface area of ​​the sample. In order to further improve the various properties of the spinel, a modified small-grain ZSM-5 zeolite core is added to form a core-shell composite material. By etching the zeolite core, the modified small-grain ZSM-5 zeolite with a huge specific surface area becomes a perfect core, allowing the spinel to grow uniformly on its surface. The surface defects of the core-shell composite material are further increased, resulting in a series of performance improvements. XPS and O-TPD2 analysis show that the concentration of oxygen vacancy defects is significantly increased and the fluidity of oxygen is greatly improved. At the same time, since the modified small-grain ZSM-5 zeolite replaces the spinel core, the crystal thickness of the spinel is greatly reduced, resulting in a significant decrease in the reduction temperature, as shown in H-TPR2. Through DFT simulation calculations, the enhancement mechanism of the modified composite material on the catalytic reaction was analyzed. The modified core-shell material is more likely to form defective oxygen vacancies, more likely to adsorb methanol molecules, and then decompose methanol into hydrogen. More importantly, the specific surface area of ​​the composite material has achieved a qualitative breakthrough. According to the BET results, the specific surface area of ​​the honeycomb core-shell structure composite nanocatalyst eventually increased to 342.763m 2 g -1 , which is about 10 times that of the initial spinel. It is precisely because of the improvement of the physical and chemical properties of the core-shell structure that the composite material shows excellent activity in the methanol degradation hydrogen production reaction. At 280°C and normal pressure, 83% of the methanol can be decomposed, and 91.3% of the hydrogen element in the degraded methanol is converted into hydrogen products. Therefore, the core-shell structure composite honeycomb core-shell structure composite nanocatalyst has achieved excellent performance in the methanol decomposition hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD pattern of the spinel sample.

[0029] Figure 2 (a) Co3O4, (b) NiCo2O4, (c) Ni 0.75 Cu 0.25 SEM images of Co2O4, (d) Ni 0.75 Cu 0.25 EDS elemental mapping and (e) quantitative analysis of Ni, Cu, Co, and O on Co2O4 catalyst.

[0030] Figure 3 Nitrogen adsorption isotherm plots and pore size distributions for (a) Co3O4, (b) NiCo2O4, (c) Ni 0.75 Cu 0.25 Co2O4.

[0031] Figure 4 XPS spectra and Gaussian fitting lines of (a) Co 2p, (b) O 1s, (c) Ni 2p, and (d) Cu2p.

[0032] Figure 5 This is the H2-TPR curve of spinel.

[0033] Figure 6 This is the O2-TPD curve of spinel.

[0034] Figure 7 XRD spectra of (a) MFI core and (b) core-shell structure composites.

[0035] Figure 8 for (a)ZSM@Ni 0.75 Cu 0.25 SEM image of Co2O4; (b) SZSM@Ni 0.75 Cu 0.25 SEM image of Co2O4; (c) MSZSM@Ni 0.75 Cu 0.25 SEM image of Co2O4; (d) MSZSM@Ni 0.75 Cu 0.25 EDS elemental mapping of Si, Al, O, Ni, Cu and Co on Co2O4.

[0036] Fig. 9 Catalyst (a) ZSM@Ni 0.75 Cu 0.25 Co2O4, (b) SZSM@Ni 0.75 Cu 0.25 Co2O4 and (c)MSZSM@Ni 0.75 Cu0.25 Isothermal adsorption diagram and pore size distribution diagram of Co2O4.

[0037] Fig.10 (a) Co 2p, (b) O 1s XPS, and (c) Ni 2P energy spectrum curves and fitting lines of core-shell materials.

[0038] Fig.11 It is the H2-TPR curve of the composite material.

[0039] Fig.12 Methanol conversion rate and stability test of the catalyst at (a) 200°C and (b) 280°C.

[0040] Fig.13 This is a test of the product (H2, CO, CO2, CH4) selectivity and stability of the catalyst at 280°C.

[0041] Fig.14 is the H2 production rate of the catalyst at 280℃.

[0042] Fig.15 These are the adsorption-desorption curves of ZSM-5, SZSM-5, and MSZSM-5. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The raw material small-grain ZSM-5 zeolite in the examples and comparative examples of the present invention has a silicon-aluminum ratio of 130 and is purchased from the catalyst plant of Nankai University with a model number of NKF-5-130FX.

[0045] Example 1

[0046] The preparation method of the honeycomb core-shell structure composite material nanocatalyst comprises the following steps:

[0047] (1) 1 gram of small-grain ZSM-5 zeolite with a grain size of 200-600 nm was added to 40 grams of a 4 wt% NaBH4 aqueous solution, heated and stirred at 80° C. for 2 hours at a speed of 300 rpm, and dried at 100° C. for 2 hours;

[0048] (2) 0.8 g of the dried product was ground to a particle size of 40-60 mesh, and then added to 40 mL of oxalic acid solution and stirred for 1 hour for acid washing. The concentration of the oxalic acid solution was 1 mol / L, and the stirring speed was 300 rpm. After drying at 100° C. for 2 hours, the product was ground again to a particle size of 200-600 nm to obtain a modified small-grain ZSM-5 zeolite, which was recorded as MSZSM-5.

[0049] (3) 0.75 mmol Ni(NO3)2·6H2O, 0.25 mmol Cu(NO3)2·3H2O, 2 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the mixture was magnetically stirred for 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0050] (4) 62 g of the obtained mixed solution was transferred to a reaction kettle, 0.6 g of the obtained modified small-grain ZSM-5 zeolite powder was added, the mixture was sealed and heated at 180° C. for 12 h, and then cooled to 25° C. from room temperature to obtain a solid material;

[0051] (5) The obtained solid material was washed 5 times with deionized water and then 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed and the centrifuged material was dried at 80 °C for 2 h and calcined at 400 °C for 2 h to obtain a honeycomb core-shell structure composite nanocatalyst, denoted as MSZSM@Ni 0.75 Cu 0.25 Co2O4.

[0052] Comparative Example 1

[0053] The preparation method of spinel Co3O4 comprises the following steps:

[0054] (1) 3 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the magnetic stirring time was 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0055] (2) 62 g of the obtained mixed solution was transferred to a reaction kettle, sealed, heated at 180° C. for 12 h, and cooled to 25° C. from room temperature to obtain a solid material;

[0056] (3) The obtained solid material was washed 5 times with deionized water and then 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed and the centrifuged material was dried at 80°C for 2 h and calcined at 400°C for 2 h to obtain spinel Co3O4.

[0057] Comparative Example 2

[0058] The preparation method of spinel NiCo2O4 comprises the following steps:

[0059] (1) 1 mmol Ni(NO3)2·6H2O, 2 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the magnetic stirring time was 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0060] (2) 62 g of the obtained mixed solution was transferred to a reaction kettle, sealed, heated at 180° C. for 12 h, and cooled to 25° C. from room temperature to obtain a solid material;

[0061] (3) The obtained solid material was washed 5 times with deionized water and then 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed and the centrifuged material was dried at 80° C. for 2 h and calcined at 400° C. for 2 h to obtain spinel NiCo2O4.

[0062] Comparative Example 3

[0063] Spinel Ni 0.75 Cu 0.25 The preparation method of Co2O4 comprises the following steps:

[0064] (1) 0.75 mmol Ni(NO3)2·6H2O, 0.25 mmol Cu(NO3)2·3H2O, 2 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the magnetic stirring time was 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0065] (2) 62 g of the obtained mixed solution was transferred to a reaction kettle, sealed, heated at 180° C. for 12 h, and cooled to 25° C. from room temperature to obtain a solid material;

[0066] (3) The obtained solid material was washed 5 times with deionized water, then washed 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed, and the centrifuged material was dried at 80 ° C for 2 h and calcined at 400 ° C for 2 h to obtain spinel Ni 0.75 Cu 0.25 Co2O4.

[0067] Comparative Example 4

[0068] ZSM@Ni 0.75Cu 0.25 The preparation method of Co2O4 comprises the following steps:

[0069] (1) 0.75 mmol Ni(NO3)2·6H2O, 0.25 mmol Cu(NO3)2·3H2O, 2 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the mixture was stirred magnetically for 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0070] (2) 62 g of the obtained mixed solution was transferred to a reaction kettle, 0.6 g of microporous zeolite ZSM-5 powder with a particle size of 500-2000 nm was added, recorded as ZSM-5, and the mixture was sealed and heated at 180° C. for 12 h, and cooled to 25° C. from room temperature to obtain a solid material;

[0071] (3) The obtained solid material was washed 5 times with deionized water and then 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed and the centrifuged material was dried at 80 °C for 2 h and calcined at 400 °C for 2 h to obtain a honeycomb core-shell structure composite nanocatalyst, denoted as ZSM@Ni 0.75 Cu 0.25 Co2O4.

[0072] Comparative Example 5

[0073] SZSM@Ni 0.75 Cu 0.25 The preparation method of Co2O4 comprises the following steps:

[0074] (1) 0.75 mmol Ni(NO3)2·6H2O, 0.25 mmol Cu(NO3)2·3H2O, 2 mmol Co(NO3)2·6H2O and 10 mmol urea were dissolved in 60 mL of a mixed solvent, wherein the mixed solvent was deionized water and ethanol in a volume ratio of 3:1, and the mixture was stirred magnetically for 25 min at a stirring speed of 300 rpm to obtain a mixed solution;

[0075] (2) 62 g of the obtained mixed solution was transferred to a reaction kettle, 0.6 g of small-grain ZSM-5 zeolite powder with a grain size of 200-600 nm, denoted as SZSM-5, and the mixture was sealed and heated at 180° C. for 12 h, and cooled to 25° C. from room temperature to obtain a solid material;

[0076] (3) The obtained solid material was washed 5 times with deionized water and then 5 times with ethanol, and then centrifuged at a speed of 4000 rpm for 3 min. The supernatant was removed and the centrifuged material was dried at 80 °C for 2 h and calcined at 400 °C for 2 h to obtain a honeycomb core-shell structure composite nanocatalyst, denoted as SZSM@Ni 0.75 Cu 0.25 Co2O4.

[0077] The present invention defines key indicators for evaluating catalytic performance: CHO3H conversion rate, CO selectivity, CO2 selectivity, CH4 selectivity, H2 selectivity and H2 yield. The H2 yield is calculated by the traditional method (conversion rate × selectivity), which represents how much hydrogen in the raw material can generate the target product H2. The specific calculation formula is shown in (1)-(6):

[0078]

[0079] H2 yield (%) = CH3OH conversion × H2 selectivity (6)

[0080] Note: The following Co3O4, NiCo2O4, Ni 0.75 Cu 0.25 Co2O4、ZSM@Ni 0.75 Cu 0.25 Co2O4、SZSM@Ni 0.75 Cu 0.25 Co2O4、MSZSM@Ni 0.75 Cu 0.25 Co2O4 are the products obtained in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 respectively.

[0081] MSZSM-5 is the small-grain ZSM-5 zeolite modified in Example 1, ZSM-5 is the microporous zeolite ZSM-5 of Comparative Example 4, and SZSM-5 is the small-grain ZSM-5 zeolite of Comparative Example 5.

[0082] (I) Catalyst characterization

[0083] The catalysts were characterized by N2 adsorption-desorption, H2 temperature-programmed reduction (H2-tpr), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS).

[0084] (1) Modified spinel materials

[0085] 1.XRD analysis

[0086] The structure of the spinel sample was analyzed by X-ray diffraction. Figure 1a. Co3O4, NiCo2O4 and Ni 0.75 Cu 0.25 The peak positions of Co2O4 spinel samples are very similar to those of AB2O4 spinel powder diffraction files in the JCPDS database. Co3O4 can be found in PDF file No. 76-1802, NiCo2O4 and Ni 0.75 Cu 0.25 Co2O4 can correspond to the file number 73-1702. Compared with NiCo2O4, Ni 0.75 Cu 0.25 The characteristic peak of Co2O4 has a slight shift, which is affected by the solid solution effect. 0.75 Cu 0.25 No diffraction peaks of NiO and CuO were found on the Co2O4 curve, indicating that Cu replaced Ni in the A position of spinel. The diffraction peaks at 2θ of 19.0°, 31.0°, 37.0°, 44.5°, 59.0° and 65.5° belong to the {111}, {220}, {311}, {400}, {511} and {440} crystal planes, respectively.

[0087] Modification from Co3O4 to NiCo2O4 and Ni 0.75 Cu 0.25 After adding Co2O4, the properties of the crystal are improved, as shown in Table 1. Figure 1 In the analysis of the main crystal plane 311 in a, the solid solution substitution disperses the characteristic peaks, and the crystallinity decreases from 62.92% (Co3O4) to 55.50% (NiCo2O4) and 53.96% (Ni 0.75 Cu 0.25 Co2O4). The decrease in crystallinity will increase crystal defects, which play a positive role in catalytic reactions. Due to the solid solution substitution effect, the crystal lattice is slightly reduced and the lattice parameters are reduced. The average grain size decreases from 20.9nm (Co3O4) to 13.7nm (NiCo2O4) and 10.7nm (Ni 0.75 Cu 0.25 Co2O4). The reduction in grain size may also lead to a reduction in particle size, which is a favorable factor for increasing specific surface area.

[0088] Table 1 Crystallinity, lattice parameters and grain size of spinel samples

[0089]

[0090] Raman spectra of spinel materials Figure 1b. AB2O4 spinel has two coordinated metal structures: AO tetrahedral structure and BO octahedral structure. The stretching vibration of the AO bond in the tetrahedron triggers a 475 cm -1 The stretching vibration of the BO bond in the octahedron leads to the peaks at 475 and 526 cm -1 The peak value appears at 475cm -1 The signal at belongs to E g Vibration mode, while 526cm -1 The signal can be attributed to the F 2g The Raman peaks of the samples show similar positions and shapes, indicating that the modified solid solution still maintains the same AB2O4 crystal structure as the original spinel, which is consistent with the XRD results.

[0091] 2. SEM and transmission electron microscopy

[0092] The particle morphology was observed by scanning electron microscopy. Figure 2 Co3O4, NiCo2O4 and Ni 0.75 Cu 0.25 SEM image of Co2O4. The three spinels first grow into a sheet-like structure, indicating that the dominant growth orientation of the lattice is consistent. But then, the layers are assembled differently. Co3O4 forms a cubic structure, NiCo2O4 layers and Ni 0.75 Cu 0.25 Co2O4 tends to assemble into flower-like structures. The morphology changes after ion substitution, indicating that the solid solution effect can lead to different assembly modes of polycrystalline particles. Different morphologies can lead to different catalyst activities. Figure 2 (ac) It can be seen that after Ni replaces Co to form NiCo2O4, the particle morphology changes from cubic to flower-like. 2+ Formation of Ni 0.75 Cu 0.25 After Co2O4, the flower-like particle size decreases. Figure 2 (d, e) show Ni 0.75 Cu 0.25 EDS mapping and quantitative analysis of Ni, Cu, Co and O elements on Co2O4 catalyst. The results show that the actual content of each element is consistent with the expected value and is very close to the theoretical value.

[0093] 3. N2 adsorption-desorption

[0094] The adsorption capacity of materials affects catalytic activity, and the adsorption performance is greatly affected by the specific surface area. Therefore, many catalyst modification operations focus on how to increase the specific surface area of ​​the material. The pore structure and pore size distribution of Co3O4, NiCo2O4 and Ni0.75 Cu 0.25 The adsorption-desorption isotherm of Co2O4 is as follows Figure 3 shown.

[0095] Co3O4, NiCo2O4 and Ni 0.75 Cu 0.25 The adsorption-desorption diagram of Co2O4 is between type IV and type V, and is more inclined to type V according to the BDDT classification, indicating that in the low pressure region, N is adsorbed as a single layer and multiple layers on the spinel surface, but the interaction between the adsorbent and the adsorbate is limited. All spinels show hysteresis loops in the high relative pressure region, which is a characteristic of mesopores. This hysteresis loop is similar to type H1, indicating that the pore size distribution of the material is relatively uniform. Figure 3 The pressure range of the hysteresis loop in (c) becomes wider, indicating that the pore size distribution increases after doping to form a solid solution. Table 2 summarizes the specific surface area and pore volume. The specific surface area of ​​the original Co3O4 is 31.1442 m 2 g -1 After continuous doping and modification, Ni 0.75 Cu 0.25 Co2O4 eventually increased to 56.1691m 2 g -1 The pore volume also increased from the initial 0.1542m 3 g -1 Increased to 0.1772m 3 g -1 The solid solution modification operation can change the assembly morphology of the crystals, and the change in morphology can significantly improve the pore structure.

[0096] Table 2 Pore structure of spinel

[0097] Spinel <![CDATA[S BET (m 2 g -1 )]]> <![CDATA[Vp(cm 3 g -1 ) a ]]> <![CDATA[D BJH (nm) b ]]> <![CDATA[Co3O4]]> 31.1442 0.1542 15.4029 <![CDATA[NiCo2O4]]> 40.4395 0.1743 14.4854 <![CDATA[Ni 0.75 With 0.25 Co2O4]]> 56.1691 0.1772 9.5837

[0098] a Adsorption volume when P / P0=0.995: b Determination by desorption branch

[0099] 4.XPS analysis

[0100] X-ray photoelectron spectroscopy was used as a measurement method to examine the valence state of the catalyst. First, Figure 4 a shows the Co 2p spectrum. The Co 2p orbital splits into Co 2p 1 / 2 and Co 2p 3 / 2 Specifically, the Co 2p curve is deconvoluted into the energy levels belonging to Co 3+ and Co 2+ Two asymmetric signals. 3+ , 2p 1 / 2 and 2p 3 / 2The main signal ranges are 777.5-782.0eV and 792.5-797.0eV respectively: for Co 2+ , 2p 1 / 2 and 2p 3 / 2 The signal peaks are between 777.5 and 785.0 eV and 793.0 and 800.5 eV, respectively. After solid solution modification, the binding energy of spinel shows a slight deviation, which is because the binding energy is affected by the chemical environment. 0.75 Cu 0.25 Co in Co2O4 3+ / Co 2+ It is significantly higher than Co3O4, indicating that the Co at the A position in Co3O4 is replaced by Ni and Cu to form NiCo2O4 and Ni 0.75 Cu 0.25 However, due to the presence of metal defects on the surface of the modified solid solution, the 0.75 Cu 0.25 A certain amount of Co is still detected on the surface of Co2O4 2+ ion.

[0101] Table 3 Co of spinel materials 3+ / Co 2+ and adsorbed oxygen / lattice oxygen

[0102] Spinel <![CDATA[Co 3+ (%)]]> <![CDATA[Co 2+ (%)]]> <![CDATA[Co 3+ / Co 2+ ]]> Oads(%) Olatt (%) Oads / Olatt <![CDATA[Co3O4]]> 41.08 58.92 0.69 59.81 40.19 1.49 <![CDATA[NiCo2O4]]> 59.07 40.93 1.44 64.72 35.28 1.83 <![CDATA[Ni 0.75 With 0.25 Co2O4]]> 61.36 38.64 1.59 66.09 33.91 1.95

[0103] The oxygen deficiency concentration can be determined from the O1s inversion curve, as Figure 4 b. The o1s asymmetric curve of spinel is decomposed into two peaks: lattice oxygen (O latt ) signal, the surface adsorbed oxygen (O ads ) signal. The Oads concentration can represent the oxygen vacancy concentration because Oads prefers to adsorb on oxygen vacancies. Table 3 summarizes the Oads / Olatt and Co deconvolution peak areas. 3+ / Co 2+ As the a-site ions are gradually replaced by Ni 2+ and Cu 2+ With the substitution, the concentration of Oads gradually increased.

[0104] The present invention detects NiCo2O4 and Ni 0.75 Cu 0.25 Ni 2p orbital binding energy and Ni in Co2O4 0.75 Cu 0.25 The binding energy of Cu 2p orbitals in Co2O4 is Figure 4cd. Similarly, the Ni 2p curve is deconvolved into two asymmetric signals, belonging to Ni 3+ and Ni 2+ It must be pointed out that Ni 3+ The generation of is not due to Ni occupying the B site. Because the b-site ion is a six-coordinated configuration, and Ni 3+ The electronic structure is 3d 7 4s 0 , cannot form a hexacoordinated d 2 sp 3 Hybrid orbital. Therefore, Ni 3+ It is attributed to the presence of oxygen vacancies. From the XPS Cu spectrum, it can be seen that Cu 2+ The presence of Cu ions in NiCo2O4 indicates that Cu ions have entered the a-position to replace Ni. As shown in Table S1, based on the deconvolution integrated peak area, Ni 3+ / Ni 2+ is 0.52. When further doped with Cu to form Ni 0.75 Cu 0.25 After Co2O4, Ni 3+ / Ni 2+ It increases to 0.71, indicating that the oxygen vacancy concentration increases after further modification.

[0105] 5.H2-TPR curve

[0106] H2-TPR method was used to detect Co3O4, NiCo2O4 and Ni 0.75 Cu 0.25 The redox ability of Co2O4 spinel. AB2O4 spinel undergoes two transformations during the TPR process: first, B 3+ Convert to B 2+ (B=Co) then B 2+ Convert to B (B = Co), followed by A 2+ Converted to A (A = Ni, Cu). The redox properties can be judged by the position of the reduction signal, such as Figure 5 As shown. Co3O4 has two peaks at 271℃ and 361℃, which are Co 3+ →Co 2+ and Co 2+ →Co process. The reduction peak of NiCo2O4 shifts to low temperature. 3+ The reduction peak shifts to 249 °C, and the peak at 332 °C belongs to Ni 2+ →Ni and Co 2+ →Co process. After solid solution modification, Ni 0.75 Cu 0.25 The redox ability of Co2O4 is further improved. 3+The reduction of the peak is reduced to 245℃, and the peak at 318℃ is similar to that of Ni 2+ →Ni and Co 2+ →The process of Co.

[0107] This result indicates that the redox properties of spinel are continuously improved after solid solution substitution, which is consistent with the decrease in XRD grain size and the change in SEM morphology.

[0108] 6.O2-TPD curve

[0109] The O2-TPD method was used to compare the active oxygen species and oxygen mobility among the spinels. Figure 6 The oxygen mobility of various spinels is different from that of other spinels. The oxygen desorption signal at around 150°C is attributed to molecular oxygen (O mol ), and the desorption peak from 280℃ to 320℃ is attributed to the surface adsorbed oxygen (O ads ), and the signal from 370℃ to 550℃ is attributed to the surface lattice oxygen (O latt,s ), and the peak above 650°C is attributed to bulk lattice oxygen (O latt,b ), first, the lattice oxygen (O latt,b ) signal is very weak at 695℃, indicating that the O in Co3O4 is very stable. 0.75 Cu 0.25 The lattice oxygen (O latt,b ) can be desorbed at about 660℃, indicating that the high temperature reaction activity of the sample has been improved. 0.75 Cu 0.25 The desorption temperature of Co2O4 keeps moving towards low temperature, which is obviously lower than that of Co3O4. Figure 6 As shown in the schematic diagram on the upper left, it shows that the low-temperature reaction ability of solid solution spinel has been improved. These phenomena indicate that Ni 0.75 Cu 0.25 The oxygen mobility of Co2O4 has become better, and the types of active oxygen have been significantly improved. This is consistent with the results of XPS O1s spectrum analysis.

[0110] (2) Core-shell structure composite materials

[0111] 1.XRD analysis

[0112] The XRD spectrum of the zeolite core is as follows Figure 7As shown in a. According to JCPDS, the diffraction patterns of ZSM-5, SZSM-5 and MSZSM-5 are completely consistent with the powder diffraction file 39-0225. The three zeolites clearly show a typical MFI framework. The crystallinity is calculated using the main crystal plane. The crystallinity of ZSM-5 is 72.12%. As the grain size decreases, the crystallinity of SZSM-5 drops to 58.51%. After modification by alkaline and acidic solutions, the pore structure tends to be regular, and the crystallinity of MSZSM is restored to 65.32%. Spinel is grown on zeolite to form a core-shell composite structure. The XRD spectrum of the composite material is shown in Figure 7 b. The catalyst not only has a spinel structure, but also has an obvious MFI-type framework. The diffraction peaks at 23.5° and 24.2° of 2θ belong to the {501} and {303} planes of the MFI framework, and the diffraction peaks at 31.0°, 37.0°, 44.5°, 59.0° and 65.5° of 2θ belong to the Ni 0.75 Cu 0.25 {200}, {311}, {400}, {511} and {400} faces of Co2O4, corresponding to file 73-1702. Compared with pure spinel, Ni 0.75 Cu 0.25 The characteristic peak of Co2O4 has a slight shift, which is affected by the crystallization environment.

[0113] Table 4 Crystallinity, lattice parameters and grain size of spinel in composites

[0114]

[0115] a According to {311} face detection: b XRD refinement results

[0116] Ni 0.75 Cu 0.25 Co2O4 grows on the surface of MFI zeolite, and the crystal properties are further improved, as shown in Table 4. Figure 1 The main crystal plane {311} analysis shows that the characteristic peak becomes diffuse and the crystallinity increases from 53.96% (Ni 0.75 Cu 0.25 Co2O4) decreased to 42.93% (MSZSM@Ni 0.75 Cu 0.25 Co2O4), which is related to the non-spinel crystal phase detected by X-ray. Due to the influence of the crystallization environment, the crystal lattice is further reduced. The average grain size is reduced from 12.0nm (Ni 0.75 Cu 0.25 Co2O4) is significantly reduced to 8.3nm (MSZSM@Ni 0.75 Cu 0.25Co2O4). The reduction in grain size may lead to an increase in grain boundaries on the particles, which is a favorable factor for the increase in defects.

[0117] 2. SEM and EDS

[0118] Figure 8 These are the morphologies of the zeolite core, spinel shell, and core-shell composite structure. Figure 8 a clearly shows the particle changes after the ZSM-5 core is combined with the spinel shell. The particles of the ZSM-5 core are rectangular and the particle size is about 600-2000nm. The spinel shell is a flower-like particle. After the spinel grows on the zeolite core, it no longer grows into a flower shape. Figure 8 b shows the Ni 0.75 Cu 0.25 Growth of Co2O4 spinel. Small-grain zeolite is also rectangular, but the particles are much smaller, only 200-500nm. And the particle size is very uniform. The original flower-shaped Ni 0.75 Cu 0.25 After Co2O4 grows on the surface of SZSM-5, it becomes a porous structure, forming a honeycomb composite material SZSM@Ni 0.75 Cu 0.25 Co2O4. Whether it is traditional ZSM-5 or small-grain SZSM-5, some spinels cannot grow on their surfaces due to their smooth particle surfaces. Therefore, we performed acid-base etching on SZSM-5. Figure 8 c As shown in the first photo, the surface of the zeolite MSZSM-5 after etching modification presents a porous structure, which is conducive to the uniform growth of spinel on the zeolite surface. Figure 8 The third picture in c shows the growth of spinel on the modified MFI surface, MSZSM@Ni 0.75 Cu 0.25 The Co2O4 sample presents a perfect honeycomb structure.

[0119] Figure 8 d shows the MSZSM@Ni 0.75 Cu 0.25 EDS mapping of Si, Al, Ni, Cu, Co, and O elements on Co2O4 catalyst. Si, Al, and O belong to the MSZSM-5 core structure, while Ni, Cu, Co, and O belong to the spinel shell structure.

[0120] 3. N2 adsorption-desorption

[0121] Many catalyst modification operations focus on how to increase the specific surface area of ​​the material to improve catalytic activity. Solid solution modification can increase the surface area of ​​spinel from 31.1442 m 2 g -1 Increase to Ni0.75 Cu 0.25 Co2O4 56.1691m 2 g -1 However, the improvement effect is still not satisfactory. Therefore, we provide MFI cores for spinel during the crystallization stage to improve the modification effect.

[0122] The adsorption-desorption curves of ZSM-5, SZSM-5 and MSZSM-5 are shown in Fig. 9 The results show that the hysteresis loops of ZSM-5 and SZSM-5 are not significant, indicating that there are fewer mesopores and more micropores in the samples. After alkali-acid modification, the hysteresis loop of MSZSM-5 becomes very obvious, indicating that the increased area after alkali-acid modification mainly comes from mesopores. The mesopore specific surface area of ​​MSZSM-5 is 127.1032m 2 g -1 Increased to 274.4244m 2 g -1 The specific surface area and pore size are summarized in Table 5. The pore size increases from 5.4918nm to 7.7740nm, and the specific surface area increases from 400.3564 to 562.2900m 2 g -1 , indicating that the pore structure performance has been greatly improved.

[0123] Table 5 Pore structure of molecular sieve core

[0124]

[0125] a Adsorption volume when P / P0=0.995: b Determination by desorption branch

[0126] MFI core structure, Ni 0.75 Cu 0.25 The adsorption-desorption isotherms of Co2O4 shell and core-shell composites are shown in Fig.10 According to the classification of BDDT, ZSM@Ni 0.75 Cu 0.25 The adsorption-desorption curve of Co2O4 is type IV with H4 hysteresis loop, and SZSM@Ni 0.75 Cu 0.25 Co2O4 and MSZSM@Ni 0.75 Cu 0.25 The graph of Co2O4 is type IV with H3 hysteresis loop. The type IV isotherm indicates that all three composite materials have obvious mesoporous structure. ZSM@Ni 0.75 Cu 0.25The H4-type hysteresis loop of Co2O4 shows an obvious microporous structure, which is related to the fact that some zeolite particles cannot be covered by spinel. 0.75 Cu 0.25 Co2O4 and MSZSM@Ni 0.75 Cu 0.25 The H3-type hysteresis loop adsorption of Co2O4 is significant, which is related to its well-developed mesoporous structure.

[0127] The specific surface area and pore volume are shown in Table 6. 0.75 Cu 0.25 The specific surface area of ​​Co2O4 is 56.1691m 2 g -1 After continuous core-shell modification, MSZSM@Ni 0.75 Cu 0.25 The specific surface area of ​​Co2O4 eventually increased to 342.763 m 2 g -1 The pore volume also increased from the initial 0.1772m 3 g -1 Increased to 0.6267m 3 g -1 The core-shell operation changes the spinel morphology and further significantly improves the pore structure properties. The huge specific surface area can provide a larger reaction surface area and active defects, which is one of the key factors to improve the catalytic activity.

[0128] Table 6 Pore structures of core, shell, and core-shell composites

[0129]

[0130] a Adsorption volume when P / P0=0.995: b Determination by desorption branch

[0131] 4.XPS analysis

[0132] XPS was used to detect Ni grown on the MFI surface. 0.75 Cu 0.25 The metallic state of Co2O4. The Co 2p orbital splits into Co2p 1 / 2 and Co 2p 3 / 2 Energy level, such as Fig.11 a. Compared with pure Ni 0.75 Cu 0.25 Compared with Co2O4, Ni grown on MFI 0.75 Cu 0.25The binding energy of Co2O4 showed a slight deviation due to the change of crystallization environment. In addition, the curve shape of the core-shell composite material also changed. 3+ The convolution line increases significantly. Co calculated by deconvolution peak area 3+ / Co 2+ For example, as shown in Table 7. 0.75 Cu 0.25 Co in Co2O4 3+ / Co 2+ The ratio increased from 1.59 to MSZSM@Ni 0.75 Cu 0.25 3.58 for Co2O4, indicating that the spinel grown on the MFI surface produces more oxygen defects, while using acid-base etched MSZSM-5 as the core can maximize the improvement of oxygen vacancies.

[0133] Fig.11 b is the O1s deconvolution curve used to detect the oxygen defect concentration. The O1s asymmetric curve of the core-shell composite material is decomposed into two peaks like pure spinel. The Olatt signal is in the range of 526.5-531.0eV, and the Oads signal is in the range of 527.0-535.5eV. It can be clearly seen that the adsorbed oxygen concentration of the composite structure is significantly increased, and the Oads / Olatt obtained from the deconvolution integral peak area is shown in Table 7. The Oads concentration increases with the addition of the MFI core structure, and the Oads / Olatt ratio increases from Ni 0.75 Cu 0.25 1.95 of Co2O4 added to MSZSM@Ni 0.75 Cu 0.25 8.22 for Co2O4, indicating that the surface oxygen vacancy concentration in the shell structure is greatly improved. These findings are consistent with the XRD results.

[0134] Ni 2p orbital binding energy spectrum Fig.11 c. Deconvolute the Ni 2p curve into the Ni 3+ and Ni 2+ According to the deconvolution integrated peak area, Ni 0.75 Cu 0.25 Ni in Co2O4 3+ / Ni 2+ The value is 0.71. 0.75 Cu 0.25 Co2O4、SZSM@Ni 0.75 Cu 0.25 Co2O4 and MSZSM@Ni 0.75 Cu 0.25 Ni in Co2O4 3+ / Ni 2+The values ​​are 0.62, 0.63 and 0.59 respectively. After the spinel is loaded into the MFI core, Ni 3+ This indicates that the increase in oxygen vacancies is not due to the absence of O atoms next to the Ni atoms, but may originate from the MFI surface within the honeycomb pores.

[0135] Table 7 Co of core-shell composite materials 3+ / Co 2+ and Oads / Olatt

[0136]

[0137]

[0138] 5.H2-TPR curve

[0139] Detection of ZSM@Ni by H2-TPR 0.75 Cu 0.25 Co2O 4, SZSM@Ni 0.75 Cu 0.25 Co2O4 and MSZSM@Ni 0.75 Cu 0.25 The redox capacity of Co2O4. Two transformations occurred during the test: Co 3+ Converted to Co 2+ and M 2+ Converted to M (M = Co, Ni, Cu). 3+ and M 2+ The reduction temperature ranges of ZSM@Ni ... 0.75 Cu 0.25 Co2O 4, SZSM@Ni 0.75 Cu 0.25 Co2O4、MSZSM@Ni 0.75 Cu 0.25 The separation peak areas of Co2O4 are 576:1629, 547:1646, and 786:2509, and the separation peak area ratio corresponds to a ratio of 1:3, which is attributed to the reaction process: AB2O4+H2→AO+2BO+H2O; AO+2BO+3H2→A+2B+3H2O. Ni 0.75 Cu 0.25 Co in Co2O4 samples 3+ and M 2+ The reduction temperature is 245℃ and 318℃, such as Figure 5 After the core-shell structure is formed, the reduction temperature of the sample is further reduced, as shown in Fig.12As shown in Figure 2, the redox performance of the core-shell catalyst was improved, among which MSZSM@Ni 0.75 Cu 0.25 Co2O4 has the best improvement effect. 3+ The reduction was reduced to 186℃, M 2+ (Ni 2+ , Cu 2+ ,Co 2+ ) shifted to 318 °C, indicating that the honeycomb structure of the core-shell material is more conducive to the reduction of metal ions.

[0140] (3) Catalytic evaluation.

[0141] Low temperature evaluation properties of spinel and core-shell composites such as Fig.13 a. It can be seen that the cubic Co3O4 has the lowest activity (9.5%). With the modification of solid solution, the catalytic activity of the flower-shaped sample gradually increases. Ni 0.75 Cu 0.25 The methanol conversion rate of Co2O4 was increased to 15.5%. After further core-shell operation, honeycomb ZSM@Ni 0.75 Cu 0.25 The methanol conversion rate of Co2O4 was further increased to 22.5%. Finally, the core-shell structure MSZSM@Ni 0.75 Cu 0.25 The methanol conversion rate of Co2O4 reached 32.5%, which is 3 times that of the initial Co3O4. The performance of spinel and core-shell catalysts evaluated at medium and high temperatures is shown in Figure 2. Fig.13 Compared with the experimental conditions shown in Figure 2, except that the temperature was increased to 280 °C, the experimental conditions remained basically the same. As the temperature increased, the methanol decomposition ability on various catalysts gradually increased. At this temperature, Ni 0.75 Cu 0.25 The methanol conversion rate of Co2O4 was increased to 52%. Once the spinel was grown on the etched modified MSZSM-5 surface and formed a core-shell honeycomb structure, MSZSM@Ni 0.75 Cu 0.25 The methanol conversion rate of Co2O4 has achieved a qualitative improvement, and 83% of methanol can be converted into H2 and other products.

[0142] The selectivity for hydrogen and other products was also studied. Fig.14 As shown, the hydrogen in methanol mainly produces hydrogen and CH4 as byproducts. The hydrogen selectivity of cubic Co3O4 is 89.5%, while the methane selectivity is 9.7%. 0.75 Cu 0.25The hydrogen selectivity of Co2O4 is 94.5%, and the methane selectivity is 4.2%, indicating that the product selectivity is optimized by solid solution modification. For the core-shell structured material, the H2 selectivity decreases slightly, while the proportion of by-product methane increases slightly. It is worth noting that the distribution of C elements in the product also changes. The selectivity of CO in the product is improved, while the generation of CO2 is suppressed. This is a favorable phenomenon if a water gas shift reaction occurs subsequently. MSZSM@Ni 0.75 Cu 0.25 The H2 selectivity of Co2O4 is 91.5%. Although the selectivity is slightly lower than that of spinel materials, considering the huge improvement in methanol conversion rate, the hydrogen production efficiency is still qualitatively optimized. Fig.15 The H2 yield is shown to increase from 37.7% for the initial spinel to 77.5% for the core-shell material MSZSM@Ni0.75Cu0.25Co2O4.

[0143] in conclusion:

[0144] The present invention uses etching modified MFI zeolite as the core to synthesize the core-shell MSZSM@Ni 0.75 Cu 0.25 Co2O4 is used as a methanol degradation catalyst. At a reaction temperature of 280°C, 83% of methanol can be decomposed, and 91.3% of the H element in the decomposed methanol can be completely converted into green product hydrogen. Combining physical and chemical property analysis and computational simulation, the excellent performance of core-shell catalysts in hydrogen production reactions was analyzed.

[0145] For spinel active materials, specific surface area and active defects are its main shortcomings. In this paper, a modified solid solution was prepared by doping and replacing the A-site of AB2O4 spinel. XRD and XPS results confirmed that the surface defects of the solid solution were significantly improved. EDS scanning spectrum confirmed that the element content in the solid solution was in line with expectations. SEM images showed that as the a-site atom was replaced, the morphology of the spinel changed from cubic to flower-like, resulting in an increase in the specific surface area of ​​the sample. In order to further improve the various properties of spinel, MFI core was added to form a core-shell composite material. By etching the zeolite core, the modified MFI with a huge specific surface area became a perfect core, allowing the spinel to grow uniformly on its surface. The surface defects of the core-shell composite material were further increased, resulting in a series of performance improvements. XPS and O-TPD2 analysis showed that the concentration of oxygen vacancy defects increased significantly and the mobility of oxygen was greatly improved. At the same time, since the modified MFI replaced the spinel core, the crystal thickness of the spinel was greatly reduced, resulting in a significant decrease in the reduction temperature, as shown in H-TPR2. Through DFT simulation calculation, the enhancement mechanism of the modified composite material on the catalytic reaction was analyzed. The modified core-shell material is more likely to form defect oxygen vacancies, which are easier to adsorb methanol molecules and then decompose methanol into hydrogen. More importantly, the specific surface area of ​​the composite material has achieved a qualitative breakthrough. According to the BET results, MSZSM@Ni 0.75 Cu 0.25 The specific surface area of ​​Co2O4 eventually increased to 342.763 m 2 g -1 , which is about 10 times that of the initial spinel. It is precisely because of the improvement of the physical and chemical properties of the core-shell structure that the composite material exhibits excellent activity in the methanol degradation hydrogen production reaction.

[0146] The disclosed embodiments are described to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a honeycomb core-shell structure composite material nanocatalyst, characterized in that: The steps include: (1) adding small-grain ZSM-5 zeolite into a NaBH4 aqueous solution, heating and stirring, and drying; (2) grinding the dried product to a particle size of 40-60 mesh, adding it to an oxalic acid solution and stirring it for pickling, and then drying it and grinding it again to a particle size of 200-600 nm to obtain a modified small-grain ZSM-5 zeolite; (3) dissolving Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O and urea in a mixed solvent at a molar ratio of 0.75:0.25:2:10, and stirring magnetically to obtain a mixed solution; (4) transferring the obtained mixed solution to a reaction kettle, adding the obtained modified small-grain ZSM-5 zeolite powder, sealing and heating, and cooling at room temperature to obtain a solid material; (5) The obtained solid material is washed with deionized water and ethanol for several times, then centrifuged to remove the supernatant, and the centrifuged material is dried and calcined in sequence to obtain the honeycomb core-shell structure composite material nanocatalyst.

2. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (1), the concentration of the NaBH4 aqueous solution is 4 wt%, and the mass ratio of the small-grain ZSM-5 zeolite to the NaBH4 aqueous solution is 1:

40.

3. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (1), the heating and stirring temperature is 80° C., the heating and stirring time is 2 hours, the heating and stirring speed is 300 rpm, the drying temperature is 100° C., and the drying time is 2 hours.

4. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (2), the concentration of the oxalic acid solution is 1 mol / L, and the mass volume ratio of the dried product to the oxalic acid solution is 0.8 g:40 mL.

5. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (2), the stirring time is 1 hour, the stirring speed is 300 rpm, the drying temperature is 100° C., and the drying time is 2 hours.

6. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (3), the mixed solvent is deionized water and ethanol in a volume ratio of 3:1, 1 mmol of urea is dissolved in 6 mL of the mixed solvent, the magnetic stirring time is 25 min, and the stirring speed is 300 rpm.

7. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (4), the mass ratio of the mixed solution to the modified small-grain ZSM-5 zeolite powder is 62:0.6, the heating temperature is 180° C., the heating time is 12 h, and the mixture is cooled to 25° C. from room temperature.

8. The method for preparing a honeycomb core-shell structure composite material nanocatalyst according to claim 1, characterized in that: In step (5), the drying temperature is 80° C., the drying time is 2 h, the calcination temperature is 400° C., and the calcination time is 2 h.

9. A honeycomb core-shell structure composite material nanocatalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the honeycomb core-shell structure composite material nanocatalyst according to claim 9 in hydrogen production by methanol degradation.

Citation Information

Cited By

  • Difunctional integral material for CO2 in-situ efficient adsorption coupling conversion and preparation method of difunctional integral material

    CN119971995A

  • A bifunctional monolithic material for in-situ efficient CO2 adsorption and coupled conversion and its preparation method

    CN119971995B